Antecedents of Relationship Quality on Commitment in the Health-Care Sector in Port Harcourt, Nigeria - Akekue-Alex; Nennaaton; Kalu; Ezema, Sylva (British Journal of Marketing Studies, 2016)
Our emphasis is to investigate the antecedent of relationship quality on commitment in the health-care sector in Port Harcourt, Nigeria. The study design takes on a cross-sectional survey with researchers adopting a quantitative research approach. 151 copies of a structured questionnaire were conveniently administered on the customers of the various hospitals and clinics in Port Harcout of which 118 copies were found useable. The measurement scale used for the three constructs of the study was modified from extant literature. Correlation coefficient and regression analysis using (SPSS 20.0 version and Gretl statistical package were employed for data analysis and testing of the proposed study model. Results point to a significant and positive relationship between antecedent of relationship quality constructs; seller provider expertise and effective communication on commitment. We therefore recommend that a physician’s expertise and his ability to communicate effectively with his clients can lead to a more committed relationship with them. What is more, such an expertise must be proven through superior skills, capabilities etc and deliberately display and communicate evidence of quality when necessity dictates. Physicians should ensure timely and accurate information are given to their clients. That is, communication must precede, follow and be concurrent with service delivery. Also, clients must open up to their doctors and share relevant information with them.